1993
DOI: 10.1002/art.1780360715
|View full text |Cite
|
Sign up to set email alerts
|

Fcγ receptor activation of neutrophils in cryoglobulin‐induced leukocytoclastic vasculitis

Abstract: Objective. The role of Fcγ receptors (FcγR) in type I cryoglobulinemia was investigated to characterize novel mechanisms of neutrophil activation in the pathogenesis of leukocytoclastic vasculitis. Methods. Neutrophils from healthy donors were incubated with purified monoclonal IgG1k cryoglobulin complexes in vitro. Changes in surface antigen expression and mechanisms of intracellular hydrogen peroxide production and calcium release were measured by flow cytometry. Results. After incubation for 2 hours, surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Cryoglobulin-induced activation of neutrophils triggered by hFcgRIIIb plays a contributory role in the pathogenesis of leukocytoclastic vasculitis [86], the dominant lesion of type-I cryoglobulinemia in human beings [130]. Clinical symptoms of type-I cryoglobulinemia include cold urticaria, Raynaud's phenomenon, cutaneous ulcers, and gangrene of the fingers and toes upon exposure to cold [131].…”
Section: Immune Vasculitismentioning
confidence: 99%
See 1 more Smart Citation
“…Cryoglobulin-induced activation of neutrophils triggered by hFcgRIIIb plays a contributory role in the pathogenesis of leukocytoclastic vasculitis [86], the dominant lesion of type-I cryoglobulinemia in human beings [130]. Clinical symptoms of type-I cryoglobulinemia include cold urticaria, Raynaud's phenomenon, cutaneous ulcers, and gangrene of the fingers and toes upon exposure to cold [131].…”
Section: Immune Vasculitismentioning
confidence: 99%
“…Cooperation of hFcgRIIIb with hFcgRIIa and CR3 is necessary for efficient phagocytosis, ADCC, and degranulation [6,84,85]. In an in vitro model of immune vasculitis hFcgRIIIb-mediated activation of neutrophils appeared to be critical for the pathogenesis of cryoglobulin-induced leukocytoclastic vasculitis [86]. mFcgRIII was first classified as an mFcgRII protein because it reacted with the same anti-FcgRII/III mAb 2.4G2 and shared with mFcgRII identical binding characteristics, interacting with mIgG1, mIgG2b, and mIgG2a in the form of immune complexes [87].…”
Section: Fcgriiimentioning
confidence: 99%
“…18 Lazzarin et al 19 studied patients with hepatitis A, B, and acute non-A and non-B hepatitis: circulating immune complexes were found in the serum of these patients with inhibitory effect upon the phagocytic activity of neutrophils. The Fcg receptors are important for phagocytic activity, and Hundt et al 20 demonstrated that, besides the cytokines, immune complexes can induce the expression of FcgRI and significantly reduced FcgRII and FcgRIII expression in the synovial fluid of rheumatoid arthritis patients. In this study, during the evaluation of the phagocytosis digestion phase by PMNs through the NBT test, a significant difference was not demonstrated among the different patients groups analyzed.…”
Section: Discussionmentioning
confidence: 99%